ChemInform Abstract: Synthesis of 6‐(Arylthio)phenanthridines by Copper‐Catalyzed Tandem Reactions of 2‐Biaryl Isothiocyanates with Diaryliodonium Salts. Issue 29 (July 2015) - Guo, Weisi; Li, Shoulei; Tang, Lin; Li, Ming; Wen, Lirong; Chen, Chao
Abstract (Arylthio)phenanthridines are prepared by tandem C—S/C—C bond—forming reaction of biaryl isothiocyanates with diaryliodonium salts using copper catalysis.